Foro: Balance y perspectivas de la modernización del sector salud - Tejada de Rivero, David (2001)
The theme of this forum is "Balance and perspectives of the modernization of the health sector." But, do we have a single concept of what health is and what the sector is? Is the sector the most convenient as a subject of analysis? What is called modernization today? Do we all agree? What elements are required to take stock? Is the term perspectives appropriate or, perhaps, is it better to refer to prospective? Faced with these questions, I have circumscribed my presentation in order to contribute with a frame of reference, because what today the French are calling the Babelization syndrome can happen to us: old concepts with new names, or old names with new concepts, and each one interpreted in a very particular way; which seems like a contradiction in a world that claims to be a communication society. In reality, these are monologues where everyone can be right, because they do not refer to the same thing.